ANALISIS PERAN, PERSEPSI MASYARAKAT DAN STRATEGI PENGUATAN DESA DALAM AKSI MITIGASI DAN ADAPTASI TERHADAP PERUBAHAN IKLIM HIDROMETEOROLOGI DI KABUPATEN BANJAR PROVINSI KALIMANTAN SELATAN - Tryana Damayanti; Emmy Sri Mahreda; Untung Bijaksana; Gusti Rusmayadi (Universitas Lambung Mangkurat, 2026)
This study analyzes the role and perceptions of communities, as well as village strengthening strategies, in mitigating and adapting to hydrometeorological climate change in three villages in Banjar Regency: Rampah, Pengaron, and Munggu Raya. The methods used included observation, interviews, participatory mapping, a Likert scale, and a SWOT analysis. The results indicate that the three villages face major obstacles in the form of low participation in policy planning, weak institutions, minimal flood management regulations, and limited budgets. However, they have significant opportunities through government support, village funds, and a culture of mutual cooperation. Community roles and perceptions are categorized as moderately influential, with an average index of 47.93, indicating strong involvement in technical aspects but still weak in strategic aspects. The SWOT analysis places all villages in Quadrant I (S-O Strategy), recommending aggressive strategies such as community capacity building, institutional strengthening, environmental conservation, and integration of climate adaptation into village development planning.